Disciplines in the making cross-cultural perspectives on elites, learning, and innovation - Lloyd, G. E. R. (Geoffrey Ernest Richard), 1933- (Oxford : Oxford University Press, 2009)
We tend to assume that our map of the intellectual disciplines is valid cross-culturally. Lloyd challenges this in relation to eight main areas of human endeavour, namely philosophy, mathematics, history, medicine, art, law, religion, and science, by examining how the disciplines were conceived and developed.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Learning and scholarship -- Cross-cultural studies; Universities and colleges -- Curricula -- Cross-cultural studies; Elite (Social sciences) -- Attitudes -- Cross-cultural studies